2009
DOI: 10.1590/s0102-311x2009001100019
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de sintomas de asma e fatores de risco associados em adolescentes escolares de 13 e 14 anos dos municípios de Tubarão e Capivari de Baixo, Santa Catarina, Brasil

Abstract: This study aimed to measure the prevalence and severity of asthma symptoms and to investigate the association between asthma symptoms and personal, geographic, and socioeconomic variables in 13-14-year-old IntroduçãoA asma é considerada uma das principais doenças da infância, sendo certamente a principal doença respiratória crônica da criança 1,2 e do adolescente 2 . A asma é caracterizada como uma reação inflamatória acompanhada de hiper-responsividade brônquica 3 , limitação variável ao fluxo aéreo, rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
5
0
3
Order By: Relevance
“…The literature adds little when it comes to the intersection between asthma and speech. In localized studies, speech is characterized as appropriate or modified without the mention of specific clinical assessment and specialized in their methods (15)(16)(17) .…”
Section: Speech Versus Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…The literature adds little when it comes to the intersection between asthma and speech. In localized studies, speech is characterized as appropriate or modified without the mention of specific clinical assessment and specialized in their methods (15)(16)(17) .…”
Section: Speech Versus Asthmamentioning
confidence: 99%
“…In order to delineate the prevalence, severity and symptoms associated with asthma, studies were conducted with children and adolescents in some Brazilian cities (15)(16)(17) . In these, among other findings, it was highlighted the presence of speech disorders in children with asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown perinatal and early life exposure to dog allergen was associated with reduced allergy and asthma risk later in life [43,44]. Renter occupied housing units were positively associated with asthma in a Brazil study [45]. Rental housing was associated with cold and damp housing, which in turn were associated with increased asthma [46].…”
Section: Discussionmentioning
confidence: 98%
“…Assim, a asma brônquica é uma doença complexa e interfere com a qualidade de vida desses doentes (Aragão, 2007;Breda, Freitas, Pizzichini, Agostinho & Pizzichini, 2009). Nessa conjetura, Matos e Machado (2007) pretenderam estudar a relação das variáveis sociodemográficas (gênero, idade e grau de instrução), clínicas (gravidade da doença, duração e tipo clínico) e psicológicas (cognições, emoções e comportamentos) com a qualidade de vida do doente asmático.…”
Section: Influência De Variáveis Biopsicossociais Em Asmáticosunclassified